Penerapan Konsep Walkable Campus pada Perancangan Jalur Pedestrian Kampus Diponegoro UKSW - Isna Nugraha Wibawa; Alfred Jansen Sutrisno (Jurnal Lanskap Indonesia, 2022)
Walkable Campus is a pedestrian track design concept that prioritizes connectivity, accessibility, security, comfort, and beauty. The UKSW pedestrian track needs to be evaluated so that it can meet the needs of users. The evaluation was carried out using the walkable campus concept, so this study aims to produce a pedestrian path design based on a walkable campus. The research method used is descriptive statistics and Scenic Beauty Estimation (SBE). Descriptive statistics were used to evaluate connectivity, accessibility, security, and convenience. While SBE is used to evaluate beauty. There are 5 spots out of 3 zones where zone 1 has 2 spots, zone 2 has 1 spot, and zone 3 has 2 spots. The results of the descriptive statistical test show that the connectivity, accessibility, security, and comfort of the 3 zones received poor ratings from users. Therefore, the results of the evaluation of user perceptions are used to make a design proposal. The proposed design is made to meet the aspects of connectivity, accessibility, security, and convenience. Meanwhile, the results of the SBE evaluation show that the aesthetic condition of the existing pedestrian paths from 5 spots has a low SBE value when compared to the 3 proposed designs. In addition, the SBE evaluation is used to determine the design recommendations. There are 5 designs that meet the walkable campus concept.